Neochelanops michaelseni (Pseudoscorpiones: Chernetidae) as potential bioindicator in managed and unmanaged Nothofagus forests of Tierra del Fuego - Lencinas, María Vanessa; Kreps, Gastón; Soler Esteban, Rosina Matilde; Peri, Pablo Luis; Porta, Andres; Ramirez, Martín; Martínez Pastur, Guillermo José (BioOne, 2021)
Bioindicators could act as early warning indicators of environmental changes, ecosystem stress or taxonomic diversity. Pseudoscorpions have rarely been used as bioindicators, due to lack of information about their ecology, habitat selection, niche preferences and requirements, especially in southern Nothofagus forests. We studied the distribution and abundance of a pseudoscorpion species, Neochelanops michaelseni (Simon 1902), in different vegetation types (Nothofagus antarctica and N. pumilio forests, grasslands and peatlands) and examined how this species responded to different forest uses (harvesting and silvopastoral management), to explore its utility as a bioindicator. The study was conducted on longterm plots located at two ranches in Tierra del Fuego, using pit-fall traps during one summer. Neochelanops michaelseni abundance was higher in Nothofagus forests than in open ecosystems, which could be attributed to their affinity for litter and coarse woody debris. In N. pumilio forests, the pseudoscorpions were sensitive to harvesting, with similar abundances in harvested forests (aggregated and dispersed retentions) and grasslands. In N. antarctica forests, differences were not detected among unmanaged and silvopastoral managed forests, probably due to higher understory plant growth, and lesser diminishing of litter and debris by thinning than by harvesting. We conclude that the pseudoscorpion, N. michaelseni, can be a good bioindicator for ecosystem conservation and for evaluating recovery rate in the ecological conditions of impacted Nothofagus forests, and that management practice intensities should be regulated to create more suitable habitats for pseudoscorpion diversity conservation.